2014
DOI: 10.1038/npp.2014.7
|View full text |Cite
|
Sign up to set email alerts
|

Parvalbumin Cell Ablation of NMDA-R1 Causes Increased Resting Network Excitability with Associated Social and Self-Care Deficits

Abstract: NMDA-receptor (NMDAR) hypofunction is strongly implicated in the pathophysiology of schizophrenia. Several convergent lines of evidence suggest that net excitation propagated by impaired NMDAR signaling on GABAergic interneurons may be of particular interest in mediating several aspects of schizophrenia. However, it is unclear which behavioral domains are governed by a net increase of excitation and whether modulating downstream GABAergic signaling can reverse neural and thus behavioral deficits. The current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 41 publications
5
105
1
Order By: Relevance
“…Thus, acute administration of ketamine or phencyclidine (PCP) enhances excitatory activity in corticolimbic structures and increases basal levels of gamma oscillations (Duncan et al, 1999;Duncan et al, 2000;Homayoun and Moghaddam, 2007;Nakazawa et al, 2012;Hunt and Kasicki, 2013;Kocsis et al, 2013). Accordingly, selective reduction of the common GluN1 NMDAR subunit in PV cells, increases basal gamma oscillations, decreases NMDAR antagonist-induced gamma oscillations, and promotes schizophrenia-associated behavioral symptoms (Belforte et al, 2010;Korotkova et al, 2010;Carlen et al, 2012;Billingslea et al, 2014). These effects could also be mediated by PV-containing interneurons in the thalamic reticular nucleus (Frassoni et al, 1991;Llinas et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, acute administration of ketamine or phencyclidine (PCP) enhances excitatory activity in corticolimbic structures and increases basal levels of gamma oscillations (Duncan et al, 1999;Duncan et al, 2000;Homayoun and Moghaddam, 2007;Nakazawa et al, 2012;Hunt and Kasicki, 2013;Kocsis et al, 2013). Accordingly, selective reduction of the common GluN1 NMDAR subunit in PV cells, increases basal gamma oscillations, decreases NMDAR antagonist-induced gamma oscillations, and promotes schizophrenia-associated behavioral symptoms (Belforte et al, 2010;Korotkova et al, 2010;Carlen et al, 2012;Billingslea et al, 2014). These effects could also be mediated by PV-containing interneurons in the thalamic reticular nucleus (Frassoni et al, 1991;Llinas et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These mice also modeled the deficits of schizophrenia patients in auditory gating in the paired tone paradigm [90,91]. Further studies demonstrated that parvalbumin (PV) interneurons in the NR1 mutants were suggested to be the crucial neuronal populations mediating the sensory gating function involved in the pathophysiology of schizophrenia [79]. Event-related potentials (ERPs) were found to be abnormal in NR1-hypomorphic mice, and thus were used as a paradigm to investigate cognitive processes, such as selective attention [61].…”
Section: Behavioral Manifestations Of Genetically Modified Nr1-mutantmentioning
confidence: 99%
“…Mice with a selective pyramidal cell knock out of NR1 have increased gamma baseline power as measured by EEG (Tatard-Leitman et al, 2015) ( Figure 2). Similarly, mice with a selective knock out of NR1 in a subset of interneurons that express the calcium binding protein parvalbumin (PV) also have a significant increase in baseline EEG gamma power Billingslea et al, 2014). Additionally, animals with a developmental knock out of NR1 in a subset of interneurons (40-50% of cortical interneurons) exhibit a high spontaneous LFP activity in the primary auditory cortex (Nakao and Nakazawa, 2014).…”
Section: Animal Models Of Schizophrenia With Relation To Resting Gammmentioning
confidence: 99%
“…For example, developmental knockdown of NR1 in a broad range of interneurons causes a decrease in short term memory . However, animals with a selective knock out of NR1 in PV interneurons have reduced working memory in some studies (Korotkova et al, 2010) but significantly improved T-maze performance in others (Billingslea et al, 2014). Thus the role of impaired interneuron function in mediating functional deficits that are associated with increased resting gamma power remains unclear.…”
Section: Relating Behavior To Eeg/lfp Validation Of Modelsmentioning
confidence: 99%
See 1 more Smart Citation